TINJAUAN YURIDIS TERHADAP PUTUSAN PENGADILAN NEGERI RENGAT NOMOR 10/Pid.B/A/2012/PN.RGT.TLK DALAM MENANGANI PERKARA ANAK BERHADAPAN DENGAN HUKUM - Anggi Fridayani Putri; Mukhlis R; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Children are integral part of human survival and the survival of a nation and state. However in the journey of life from the children, sometimes the children are not always have good experience, even the children as a criminal, they must against the law. The children who make a crime, they also become a victime because the functions of tri education center are not worked. In this case, the judges have make the criminal sanctions for the children are not suitable with community research from Bapas Pekanbaru and the other regulations.In this research, there are two problems. First how are the judges make considerant from the case of number 10/Pid.B/A/2012/PN.RGT.TLK?. Second, what is the legal basic from the case of number 10/Pid.B/A/2012/PN.RGT.TLK?.There are four research methodes. First, the types of research is the normative legal research which discuss about synchcronization level of law, in this case, discuss about the judges handle children as a criminal which connected with the regulation. Second, the data sources are second data which supported by primary legal material, secondary legal material and legal material tertiary. Third, data collection techniques use review of the literature. Fourth, after the datas have comes, analyzed qualitatively.From the research problem, there are two main things that can be inferred. First, the considerant from the case of number 10/Pid.B/A/2012/PN.RGT.TLK among are the children who make narcotics crime which is not suitable with article number 111 paragraph (1) the law of narcotics number 35 of 2009 jo. article number 55 paragraph (1) to 1 the book of criminal law jo. the law of juvenile justice number 3 of 1997 and the indictment of prosecutor which is an alternative, so the judges choose first indictment. Second, the legal basic from the case number 10/Pid.B/A/2012/PN.RGT.TLK are article number 111 paragraph (1) the law of narcotics number 35 of 2009 jo. article number 55 paragraph (1) to 1 the book of criminal law jo. the law of juvenile justice number 3 of 1997. The writers suggest, the judges give the sanctions, they must look the future life from the children with they order the prosecutors are still oversee them that the children don’t do criminal again next time and if the children are proven to do the crime, the judges must give a sanction is supervision criminal for them, not give a penalties criminal.